Research on the Cultivation of Composite Industrial Design Talents in Local Applied Undergraduate Colleges and Universities - Wang, Fang (International Journal of Scientific Research and Management (IJSRM), 2024)
The cultivation of industrial design talents should arrive at the social kernel problems in the new era, and the research should shift from “discipline-oriented” to “problem-oriented” and “demand-oriented”, and take a cross and comprehensive perspective to examine the discipline orientation and talent cultivation objectives of industrial design in the new era. It examines the disciplinary positioning and talent cultivation objectives of industrial design in the new era, plans the high-quality development path of industrial design education in applied undergraduate colleges and universities from multiple perspectives such as co-creation of teachers and students, cultural leadership, digital intelligence empowerment, and multi-dimensional integration, etc., and combines the disciplinary foundation and characteristics of the institutions and the advantageous industrial resources of the local industry to build a modularized curriculum system of cross-disciplinary integration and a diversified innovative ecology of design talent cultivation, thus building a differentiated innovation paradigm for design disciplines in applied undergraduate colleges and universities，effectively enhance the composite vocational core quality of industrial design talents in local applied undergraduate colleges and universities as well as local service consciousness, so as to provide solid support for the sustainable development of regional economy and society.